Perbandingan Keterampilan Komunikasi Oral Siswa melalui Penerapan Model Kooperatif Tipe Jigsawd an Tipe Reciprocal Teaching (RT) dalam Pembelajaran Biologi - Ulfa, Amalia; Indrowati, Meti; Maridi, Maridi (Universitas Sebelas Maret, 2019)
This research aims to:examin the comparation of student’s oral communication skills between the implementation of cooperative learning model of Jigsaw and Reciprocal Teaching (RT) on biology learning of grade XI for majoring in science of SMAN 2 Karanganyar. This research is quantitatif research and tend quasy-experimental. The research design used was posttest only group design. The sampling technique used cluster sampling. The population of this research is all students of grade XI for majoring in science of SMAN 2 Karanganyar in the academic year 2018/2019. Selected sample of this study were grade XI science 4 as the experimental group 1 that used Jigsaw cooperative learning model and grade XI science 2 as the experimental group 2 that used RT cooperative learning model. The techniques for collecting data using observation sheets and documents of school. Data was analyzed by the independent sample test, calculations used SPSS 25 with the significance level of 5% (α = 0,05). The results of independent sample test show the value of sig. 0,011 < 0,05, so it can concluded that there is difference of student’s oral communication skills between the implementation of cooperative learning model of Jigsaw and Reciprocal Teaching (RT) on biology learning of grade XI for majoring in science of SMAN 2 Karanganyar. The average value of student’s communication skills of the experimental group 1 with the implementation of Jigsaw cooperative learning model is higher then the experimental group 2 with the implementation of RT cooperative learning model, which is 64,98 (high category) > 59,13 (medium category).